INNATE IMMUNITY: MECHANISMS OF REALIZATION AND PATHOLOGICAL SYNDROMES. PART IV - P.F. Litvitsky; T.G. Sinel’nikova (Вопросы современной педиатрии, 2009)
The lecture discuss the role and mechanisms of cytokines’ effect realization as significant and integrating factors of nonspecific organism’s defense system; it characterizes main cytokine’s classes, its effects in normal state and in conditions of development of different disorders. Authors analyze etiology, pathogenesis, and signs of syndromes of organism’s immunobiological surveillance insufficiency, developing as a result of cytokine’s control mechanism disorder. The conclusion on lectures is presented.Key words: cytokines, innate immunity, syndromes of innate immunity insufficiency.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(4):95-101)